TEACHER SELF-EFFICACY IN RURAL THAILAND: INSIGHTS FROM PRE-SERVICE ENGLISH TEACHERS’ PRACTICUM EXPERIENCES - Choephatruedi, Sumit; Inpin, Bhornsawan (LLT Journal: A Journal on Language and Language Teaching, 2025)
This qualitative case study investigates how pre-service English teachers (PSETs) develop teacher self-efficacy (TSE) during teaching practicums in Thai rural schools. Grounded in Bandura’s social cognitive theory, the study examines the role of mastery experiences, vicarious learning, social and verbal persuasion, and emotional states in shaping TSE. Six final-year PSETs from a northern Thai university were purposefully selected to represent diverse perceptions of efficacy. Data were gathered through semi-structured interviews, classroom observations, and self-reflections, and analyzed inductively using a multi-phase coding process. The results reveal that PSETs’ self-efficacy developed through a dynamic and non-linear process. At the beginning, participants experienced mixed emotions and “reality shock,” including resource shortages, multigrade classes, and limited mentorship. Over time, their TSE was strengthened through instructional successes, modeling from experienced teachers and peers, constructive feedback, and emotional resilience. These findings contribute to teacher education research by deepening understanding of TSE development in under-resourced contexts and offering practical implications for designing practicum programs that build professional competence and identity. It also highlights the need for teacher education to prepare PSETs for rural placements, equip mentors to provide targeted support, and promote reflective practices for emotional resilience.